Digitization of accounting for small enterprises - V.V. (Економіка, управління та адміністрування, 2023)
The article is devoted to the problem of forming a digital accounting environment of small enterprises. The purpose of the article is to establish the impact of digitalization as a global vector of accounting development on the work of small enterprises. Digitization play the main role in the development and long-term survival of small enterprises. It allows them to process and structure data quickly, make business information personalized. Digitalization has changed both accounting technology and the components of its method. The 2019–2023 coronavirus pandemic and the war in Ukraine only accelerated the transition of accounting to a digital format that allowed working remote. The analysis of scientific works shows that the following are the components of digitalization of accounting: use of specialized software, in particular, cloud technologies; electronic document flow in XBRL format; application of artificial intelligence, analytical platforms, in particular, BigData, blockchain for modelling, analysis and control of activities; electronic payment systems, electronic trading platforms, electronic platforms for business, etc. The main problems of digitalization of small enterprises are the cost of software and computer equipment, the qualification of accounting specialists, ensuring the security of data in digital format. There are a number of obstacles to the introduction of electronic document management in the XBRL format. Differences in national accounting practices do not allow for comparability of documents. The distant prospects of obtaining benefits from the XBRL format reduce the motivation for its implementation. The translation of the XBRL taxonomy takes a long time. Disclosure of non-financial information causes certain difficulties. According to the results of the study, it was determined that better structuring of accounting information directs small enterprises to realize their own potential due to the disclosure of available resources, their structure, as well as the expansion of opportunities for their full, rational and effective use to achieve the set goals.